Studi Kemampuan Penyerapan Panas pada Atap Rumah Seng Berwarna Terhadap Intensitas Matahari dalam Mengatasi Global Warming - Nazaruddin, Nazaruddin; Zulfadli, Teuku; Mulkan, Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The environmental temperature has increased significantly reaching 33oC as felt by the community, one of which is in the Aceh region which triggers Global Warming. As a result of the increase in temperature in the Aceh area, many buildings and houses become uncomfortable especially during the daytime because most house with zinc roof. This will cause the temperature in the house and the air around it to increase. Therefore, it is necessary to do research on the study of heat absorption on colored zinc roofs. This research method is to calculate the heat absorption (sun intensity) in zinc that has been coated with several kinds of colors such as white, red, blue, yellow and black. The purpose of this study was to determine the color that has the least amount of heat absorption to the sun's intensity. The highest room temperature on zinc-coated black is 49.2° C and the lowest is in white. 40.9°C from the pen. In the environmental temperature observation, there is the highest temperature at 12.00. Room temperature increased the highest temperature at 12.00 on black zinc. The distribution of room temperature can be averaged with a yellow color of 46.0°C, a black color of 49.2°C, a blue of 45.5°C and a white zinc of 40.9 oC. The heat absorbed in the room is 47.9 joules, so from the overall average of the test it can be described that the room temperature is 45.6 and the zinc temperature is 53.8oC from the highest temperature difference at 12.00 WIB, room temperature and 13.00 WIB the highest absorption occurs at zinc temperature.